The forgotten four : breaking the color barrier in pro football - Smith, Elliott, 1976- (Black trailblazers in sports (Lerner Publications Company), 2025)
"Millions of people watch the NFL every year, but Black men weren't always allowed to play. Learn about the NFL's beginning, football's Forgotten Four, and football players' ongoing fight for racial justice"--